2019
DOI: 10.21608/mjmr.2022.221988
|View full text |Cite
|
Sign up to set email alerts
|

The role of different fetal pulmonary artery Doppler indices in the prediction of neonatal respiratory distress syndrome

Abstract: Objective: To study whether fetal main pulmonary artery (MPA) Doppler indices can predict the development of neonatal respiratory distress syndrome (RDS). Study Design: This Observational Prospective cohort study included pregnant women between 28-and 40-weeks gestation. The diagnostic accuracy of MPA Doppler measurements (pulsatility index (PI), resistance index (RI) and acceleration time/ejection time (At/Et)) for diagnosis of neonatal RDS was tested by comparing the Doppler findings with the clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As the main imaging examination method of NRDS, chest X-ray has the advantages of simple operation and convenient use, but it lacks specificity in the early stage. In addition, it is easy for clinicians to have errors in judging the condition [ 23 ]. Moreover, X-ray examination has ionizing radiation and newborns are particularly sensitive to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main imaging examination method of NRDS, chest X-ray has the advantages of simple operation and convenient use, but it lacks specificity in the early stage. In addition, it is easy for clinicians to have errors in judging the condition [ 23 ]. Moreover, X-ray examination has ionizing radiation and newborns are particularly sensitive to it.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, X-ray examination has ionizing radiation and newborns are particularly sensitive to it. In order to understand the recovery of the lungs, chest X-ray examination is often needed, which will inevitably lead to high ionizing radiation damage due to many times of X-ray examination [ 23 , 24 ]. Therefore, there is an urgent need for efficient, convenient, and safe examination methods to study the pulmonary condition of NRDS infants [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Between PI and RI, there was no statistically significant difference. Using a threshold of 0.3 for At/Et, the existence of RDS was predicted (sensitivity: 77.78 percent , specificity: 83.87 percent) [14]. Elkhalik and his colleague found that 46 (23%) of the fetuses had RDS (+ve) whereas 154 (77%) did not (-ve).…”
Section: Fig (1) Incidence Of Rds and Nicu Admission In All Studied C...mentioning
confidence: 99%